2008
DOI: 10.1897/ieam_2007-050.1
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to the hazard classification of alloys based on transformation/dissolution

Abstract: Most of the metals produced for commercial application enter into service as alloys which, together with metals and all other chemicals in commerce, are subject to a hazard identification and classification initiative now being implemented in a number of jurisdictions worldwide, including the European Union Registration, Evaluation, Authorisation and Restriction of Chemicals (REACH) initiative, effective 1 June 2007. This initiative has considerable implications for environmental protection and market access. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 10 publications
4
14
0
Order By: Relevance
“…The reason is most probably combined effects of particle agglomeration (more commonly occurring for small-sized particles), confirmed by the light diffraction measurements for small particles, and/or a thermodynamic equilibrium shift between released metal ionic species in solution and the metal surface in the closed experimental system (smaller particles are releasing more dissolved metal into solution, which then decreases further dissolution due to thermodynamic considerations). Similar effects have been observed in other biological systems [10,13,18,20,24]. Particle agglomeration has previously been shown to decrease the initial release of copper from non-sonicated copper metal nanoparticles compared with sonicated particles [23].…”
Section: Discussionsupporting
confidence: 72%
“…The reason is most probably combined effects of particle agglomeration (more commonly occurring for small-sized particles), confirmed by the light diffraction measurements for small particles, and/or a thermodynamic equilibrium shift between released metal ionic species in solution and the metal surface in the closed experimental system (smaller particles are releasing more dissolved metal into solution, which then decreases further dissolution due to thermodynamic considerations). Similar effects have been observed in other biological systems [10,13,18,20,24]. Particle agglomeration has previously been shown to decrease the initial release of copper from non-sonicated copper metal nanoparticles compared with sonicated particles [23].…”
Section: Discussionsupporting
confidence: 72%
“…T/D reaction kinetic data were generated for 3 tungsten carbides of different measured specific surface areas in order to calculate the critical surface area. This approach is consistent with similar correlations of 7‐d metal concentrations to surface area loadings for Ni metal and several alloys that were reported previously (Skeaff et al ).…”
Section: Resultssupporting
confidence: 92%
“…Because details of the T/DP experimental procedure, including cleaning of glassware, methods of agitation and temperature control, aqueous medium compositions, pH control, pH and dissolved O measurement, sampling procedure, and calculation of net concentrations have been presented previously (Skeaff et al , , ; Huntsman‐Mapila et al ), only aspects of the present procedure that differed from those already reported are presented. The UN T/DP (UN ) was followed, which calls for agitating weighed quantities of the substance of interest in 1 L of aqueous medium based on the OECD 203 medium for ecotoxicity testing (OECD ) in the temperature range 20 to 23 °C, sampling at specified intervals, and determining the concentrations of the dissolved analytes of interest.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…We have previously presented in some detail the T/DP experimental procedure, including methods of agitation and temperature control, aqueous media compositions, pH control, pH and dissolved O 2 measurement, and sampling procedure (Skeaff et al 2008, 2011). Essentially, the experimental procedure involves agitating weighed quantities of the test substance in 1 L of aqueous media based on the OECD 203 medium for ecotoxicity testing (OECD 1992) in the temperature range 20°C to 23°C, followed by sampling and analyzing the solutions for the metals of interest.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…We have outlined the GHS aquatic hazard classification framework, scheme, and applications for metals, metal compounds, and alloys in previous publications (Skeaff et al 2008, 2011). Essentially, comparisons of selected acute ecotoxicity reference values (ERVs) with dissolved metal concentrations released at specified intervals under standard transformation/dissolution (T/D) conditions (Skeaff et al 2006; UN 2011) into standard aqueous media from mass loadings of 1, 10, and 100 mg/L of the test substance establish the corresponding Acute 1, 2, and 3 hazard classification levels of the scheme.…”
Section: Introductionmentioning
confidence: 99%